2011
DOI: 10.1063/1.3595740
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of W-shaped rib roughened solar air heater

Abstract: Artificial rib roughness is a convenient method for enhancing thermal performance of solar air heater. An experimental investigation has been carried out to study the thermo-hydraulic performance of solar air heater using W-shaped ribs on absorber plate, the roughened wall being heated while the remaining three walls being insulated. W-shaped ribs have been tested both pointing downstream (W-down) and upstream (W-up) to the flow. The roughened wall has relative roughness height (e/D h ) of 0.03375, relative ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Similarly, Kumar et al [83] and Mittal et al [216] showed how exergetic efficiency (η exg ) varies with Re and ∆T/I. The design plots for artificially roughened SAH duct parameters, as shown in Figures 47 and 48, were provided by investigators [199,209,216] compared for different SAH ( [20,41,143,147,160,163,181]). These design graphs reveal the roughness parameter's optimal values.…”
Section: Thermo-hydraulic Performance Of Artificially Roughened Sahmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, Kumar et al [83] and Mittal et al [216] showed how exergetic efficiency (η exg ) varies with Re and ∆T/I. The design plots for artificially roughened SAH duct parameters, as shown in Figures 47 and 48, were provided by investigators [199,209,216] compared for different SAH ( [20,41,143,147,160,163,181]). These design graphs reveal the roughness parameter's optimal values.…”
Section: Thermo-hydraulic Performance Of Artificially Roughened Sahmentioning
confidence: 98%
“…2022, Elsevier. (b) η exg vs. Re for different SAH ([20,41,147,160,163,181]); reprinted with the permission from ref [156],. 2022, Elsevier.…”
mentioning
confidence: 99%
“…Lanjewar et al [44] done an experiment to study the thermo-hydraulic performance of SAH using W-shaped ribs on absorber plate. W-shaped ribs have been investigated under downstream and upstream condition.…”
Section: W Shaped Ribsmentioning
confidence: 99%
“…The authors have studied much research to understand the physics behind rib turbulators and flow regimes. It is found that few of the researchers accomplished their exertion on the roughness geometry of arc shape, 13 square ribs, 14 broken arc, 15 continuous W‐shaped, 16 discrete W‐ribs, 17 winglet shape, 18 Delta winglet, 19 chamfered grooved type, 20 conical shape, 21 and S‐shaped 22 which have improved the thermal performance of SPAH. Many of the investigators also executed their research work in V‐shaped rib roughness so that more generation of secondary flow could be assessed to augment the desired heat transfer rate and thermal efficiency rate.…”
Section: Introductionmentioning
confidence: 99%